Chronotype, Sleep, and Depressive Symptoms Among Chinese College Students: A Cross-Sectional Study - Li, Tingting; Xie, Yang; Tao, Shuman; Yang, Yajuan; Xu, Honglv; Zou, Liwei; Tao, Fangbiao; Wu, Xiaoyan (Frontiers in Neurology, 2020)
Objective: To describe the prevalence of chronotype and depressive symptoms among Chinese college students, and to examine the association between chronotype and depressive symptoms. Method: From April to May 2019, a cross-sectional survey was conducted among 1 179 Chinese college students from 2 universities in Anhui and Jiangxi provinces, respectively. A total of 1 135 valid questionnaires were collected, the valid response rate was 98.6%. The questionnaire investigated age, gender, height, weight, only child status, residential background, self-reported family economy, and self-reported study burden. The chronotype was assessed by the Morning and Evening Questionnaire (MEQ). Depressive symptoms and sleep quality were evaluated by the Patient Health Questionnaire 9 (PHQ-9) and the Pittsburgh Sleep Quality Index (PSQI), respectively. A chi-square test was used to examine the proportion of depressive symptoms among Chinese college students with different demographic characteristics. The generalized linear model was used to analyze the relationships between chronotype and depressive symptoms. Results: The proportion of morning types (M-types), neutral types (N-types), and evening types (E-types) of college students were 18.4%, 71.1%, and 10.5%, respectively. The proportion of mild depression, moderate depression, and moderate to severe depression of participants were 32.4%, 6.0%, and 4.2%, respectively. Compared to the M-types, after controlled for age, gender, sleep quality, perceived study burden, father's education level, and perceived family economy, depressive symptoms were positively correlated with E-types (OR=2.12, 95% CI:1.35~3.33). Conclusions: There was a significant association between chronotype and depressive symptoms among Chinese college students. Further longitudinal studies were needed to clarify the causal relationship between chronotype and depressive symptoms.